Habitual caffeine consumption does not affect the ergogenicity of coffee ingestion during a 5 km cycling time trial - Clarke, N. D.; Richardson, D. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
There is growing evidence that caffeine and coffee ingestion prior to exercise provide similar ergogenic benefits. However, there has been a long-standing paradigm that habitual caffeine intake may influence the ergogenicity of caffeine supplementation. The aim of the present study was to investigate the effect of habitual caffeine intake on 5-km cycling time-trial performance following the ingestion of caffeinated coffee. Following institutional ethical approval, in a double-blind, randomized, crossover, placebo-controlled design, 46 recreationally active participants (27 men and 19 women) completed a 5-km cycling time trial on a cycle ergometer 60 m in following the ingestion of 0.09 g/kg coffee providing 3 mg/kg of caffeine, or a placebo. Habitual caffeine consumption was assessed using a caffeine consumption questionnaire with low habitual caffeine consumption defined as <3 and =6 mg · kg-1 · day-1 defined as high. An analysis of covariance using habitual caffeine intake as a covariant was performed to establish if habitual caffeine consumption had an impact on the ergogenic effect of coffee ingestion. Sixteen participants were classified as high-caffeine users and 30 as low. Ingesting caffeinated coffee improved 5-km cycling time-trial performance by 8 ± 12 s; 95% confidence interval (CI) [5, 13]; p < .001; d = 0.30, with low, 9±14 s; 95% CI [3, 14]; p = .002; d = 0.18, and high, 8 ± 10 s; 95% CI [-1, 17]; p = .008; d = 0.06, users improving by a similar magnitude, 95% CI [-12, 12]; p = .946; d = 0.08. In conclusion, habitual caffeine consumption did not affect the ergogenicity of coffee ingestion prior to a 5-km cycling time trial.